Differential Yield of Pathogens from Stool Testing of Nosocomial versus Community-Acquired Paediatric Diarrhea - Savita Deorari; Athena McConnell; Kah-Kee Tan; Nadeem Jadavji; Doreen Ma; Deirdre Church; Gary Katzko; D Grant Gall; Taj Jadavji; H Dele Davies (Canadian Journal of Infectious Diseases)
OBJECTIVES: To evaluate the role of routine stool examination for all pathogens in paediatric nosocomial diarrhea (NAD) and community-acquired diarrhea (CAD) over a two-year period at Alberta Children’s Hospital and current practices in other Canadian hospitals. A secondary objective was to characterize features that may predict NAD or CAD etiology.